A comparative analysis of melodic rhythm in two corpora of American popular music. Issue 2 (4th May 2022) - White, Christopher William; Pater, Joe; Breen, Mara
Abstract : This paper compares two corpora of melodies drawn from premillennial and postmillennial American popular music, and identifies several notable differences in their use of rhythm. The premillennial corpus contains melodies written between 1957 and 1997 [deClercq and Temperley (2011. "A Corpus Analysis of Rock Harmony." Popular Music 30 (1): 47–70)], while the postmillennial corpus (compiled for this study) consists of songs popular between 2015 and 2019. For both corpora, we analysed (1) the distribution of note onsets within measures; (2) the distribution of four-note rhythmic cells, (3) the speed of melodic delivery, and (4) the tempo of the tactus. Our analyses indicated that the postmillennial melodies are delivered more quickly, are distributed more evenly throughout their measures, repeat rhythmic cells more frequently, and are annotated at slower tempos. Even when the tactus tempos were standardized into an allowable window of 70–140 BPM, this effect, though smaller, remained. We then use our techniques to observe the properties of three representative postmillennial tracks, finding that salient information can be located in both standardized and non-standardized tactus data, and that tempo-variant differences between corpora are closely connected to musical genre, with music designated as "pop" being more similar over both genres, and postmillennial rap and hip-hop introducing the most uniqueness.